Portrayal of a business leader by different media. - Hong, Bee Ping. (2008)
Steve Jobs, the CEO of Apple Computer is a leader highly admired for his charismatic and enigmatic leadership. In this exploratory research, we want to examine his construction by the media and find out if there are significant differences in the portrayal of the same business leader by the two countries’ media, perhaps a result of each country’s cultural beliefs and principles.